(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In our research work we have synthesized new kinds of anticorrosion inhibitor based on cucurbit[n]urils. It was investigated effect of cucurbit[n]urils’ concentration on anticorrosion inhibition mechanism on the №3 steel surface. During this experiment it was used thermodynamic methods.